The Effect of Misspellings on Information Retrieval in Online Public Access Catalogues - Willson, Rebekah; Given, Lisa M. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Spelling is an important literacy skill, crucial to successful searching in Online Public Access Catalogues (OPACs). Students at the University of Alberta, were given 4 search tasks. They were given a topic and asked to find as many items on that topic in the OPAC as possible. They were allowed ... L’orthographe est une compétence d’alphabétisation importante, de même qu’un facteur essentiel de succès de la recherche dans les catalogues interrogeables en ligne (CIELs). Les étudiants de l’Université de l’Alberta ont reçu 4 tâches de recherche. Pour chaque tâche, ces derniers devaient retrouver un maximum de notices traitant de ce sujet dans le CIEL. Les étudiants pouvaient…